Metode Sol Gel Untuk Mengekstraksi Silika Dari Abu Sekam Padi - Rosmiyani, Tia; Sari, Trisna Kumala; Alizar, Alizar; Mulia, Melindra (Departemen Kimia FMIPA UNP, 2023)
Rice husk ash (RHA) is a lignocellulosic material such as biomass in other materials that also contain silica. Amorphous silica obtained from rice husk ash is thought to be an important source that can produce silicon carbide, pure silicon and silicon nitride flour. Rice husk ash contains high silica (>60%). Gel silica is ekstracted by adding sodium hydroxide to produce a sodium silicate solution. The silica extraction was carried out by reacting the rice husk ash using 1M NaOH solution at 80°C for 1 hour. Subsequently, it was added 1M HCl to pH 7. Then it was evaporated in an oven at 80°C to constant weight. Based on the results of the FTIR analysis, the absorption peak of silica with a wavelength of 1070.17 cm-1 is similar to the absorption peak of 98% silica with an absorption wavelength of 1054.95 cm-1. The extracted gel silica has an amorphous crystalline form where in the XRD test there is an absorption peak that widens in the range of 2θ = 22